Colmare il divario: Performatività e transdisciplinarità - Carlotti, Edoardo Giovanni (Mimesis Journal, 2017)
Francesco Chillemi’s L’infondamento, an essay on performing arts and literature as a means to approach seminal questions in contemporary philosophical research, extensively deals with the issues of auto-referentiality and self-reflection in the sciences and the humanities. Luigi Pirandello’s Sei personaggi in cerca d’autore, Elsa Morante’s Menzogna e sortilegio and Carmelo Bene’s Amleto (da Shakespeare a Laforgue) are studied as outstanding examples of how artistic creation may “perform” a discourse about itself, and explore epistemological domains usually thought to be open to investigation only by the scientific method. Thus, transdisciplinarity as an “interchange practice”, founded on dialogue and mutual awareness, can help to bridge the gap between different disciplines which nevertheless share the same object of research.